2017
DOI: 10.1039/c7tb01063j
|View full text |Cite
|
Sign up to set email alerts
|

A series of terpyridine-based zinc(ii) complexes assembled for third-order nonlinear optical responses in the near-infrared region and recognizing lipid membranes

Abstract: Two-photon (TP) microscopy has advantages for biological imaging in that it allows deeper tissue-penetration and excellent resolution compared with one-photon (OP) microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…[29,30] As shown in Figure S2 and S3 (SI), Φδ decreased in DPPC, Raft Mix and DOPC order (1350 (DPPC), 975 (Raft Mix) and 67 GM (DOPC)). These values are much larger than Φδ value of CL2 in DPPC" [18] and was the largest among reported TPF lipid raft probes.. [14][15][16][17][18] Maximum two-photon excitation wavelengths (λ EM TP ) were 780, 790 and 800 nm, respectively. It can be seen that, Φδ increased upon the increase of medium viscosity (Figure S3, SI), and Φδ in DPPC was more than 20 times more than that in DOPC.…”
Section: Relationship Between Two-photon Action Cross Section Of Dlr and Its Two-photon Excitation Wavelengthmentioning
confidence: 80%
See 1 more Smart Citation
“…[29,30] As shown in Figure S2 and S3 (SI), Φδ decreased in DPPC, Raft Mix and DOPC order (1350 (DPPC), 975 (Raft Mix) and 67 GM (DOPC)). These values are much larger than Φδ value of CL2 in DPPC" [18] and was the largest among reported TPF lipid raft probes.. [14][15][16][17][18] Maximum two-photon excitation wavelengths (λ EM TP ) were 780, 790 and 800 nm, respectively. It can be seen that, Φδ increased upon the increase of medium viscosity (Figure S3, SI), and Φδ in DPPC was more than 20 times more than that in DOPC.…”
Section: Relationship Between Two-photon Action Cross Section Of Dlr and Its Two-photon Excitation Wavelengthmentioning
confidence: 80%
“…[12,13] A two-photon microscope (TPM) [10,11] excited by two near-infrared photons, can achieve real-time dynamic three-dimensional (3 D) imaging of microscopic objects, and provide sharp tools for biological research of lipid rafts. [12][13][14][15][16][17][18] An efficient bioimaging TPF probe, it should have a large two-photon action cross-section (δΦ). However, the δΦ values of previously reported TPF lipid raft probes were relatively small, for example CL2, [18] its δΦ in DPPC (dipalmitoylphosphatidylcholine) was only 80 GM (1 GM � 10 À 50 cm 4 .s/photon).…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al reported at wo-photona ctive donor-acceptor (D-A) terpyridine ligand system and as eries of its corresponding four Zn II complexes (Scheme 2, complexes 8 and 9). [54] The systematicp hotophysical examinations employed by Tian's group showedt hat for the symmetrical complex 9,t he third-order NLO response was found to increase significantly more in the NIR than the other asymmetricc omplexes(8-1, 2, 3). To further investigate the application of such complexes in living systems, complex 9 was designated as at wo-photon fluorescent probe for cellular lipid membranes.T he imaging results of complex 9 presented that the cells showeds trong fluorescences ignal both in one-and two-photonchannels (Figure2A).…”
Section: Membranelabelingmentioning
confidence: 99%
“…Tian et al. reported a two‐photon active donor‐acceptor (D‐A) terpyridine ligand system and a series of its corresponding four Zn II complexes (Scheme , complexes 8 and 9 ) . The systematic photophysical examinations employed by Tian's group showed that for the symmetrical complex 9 , the third‐order NLO response was found to increase significantly more in the NIR than the other asymmetric complexes ( 8‐1 , 2 , 3 ).…”
Section: Bioimaging Applications Of Znii Complexesmentioning
confidence: 99%
“…In contrast to noble metal analogues, similar investigations with low-cost 3d metals are much less in literature [57][58][59]. Although, Zn(II)-terpyridine complexes appended with one or more stilbene moiety are reported with regard to the design of efficient two-photon probes for bioimaging [60] and improvement of second-order nonlinear optical (NLO) responses [61], no report dealing with their photo-isomerization aspects are available in the literature. Herein, we address the influence of solvents and the effect of electron donating/withdrawing substituent (X) on their optical properties as well as thermodynamic and kinetic features of photoisomerization procedure.…”
Section: Introductionmentioning
confidence: 99%